Large‐Area Wire Grid Polarizer with High Transverse Magnetic Wave Transmittance and Extinction Ratio for Infrared Imaging System. Issue 2 (8th December 2022) - Wang, Chongyu; Chao, Yinyin; Liang, Jiujiu; Yan, Bing; Wang, Xiaohao; Ni, Kai; Zhou, Qian
Abstract : Infrared (IR) wire grid polarizer is the core device of polarization imaging system with exceptional properties. However, the fabrication of high‐quality devices with large area and good uniformity remains challenging. Herein, a new high aspect ratio structure is designed and fabricated, which makes the polarizer have high transverse magnetic (TM) transmittance and extinction ratio in a wide wavelength band. This study also presents some innovations to traditional fabrication processes. These improvements make it easier to fabricate polarizers with good performance as well as large areas. In a very wide wave band (3–15 μm), the extinction ratio is over 32.33 dB. The average TM transmittance of the wire grid layer is 80%, and of the polarizer is 56.57%, which is almost the highest on silicon substrate without antireflection (AR) coating. Meanwhile, the diameter with good uniformity is larger than 30 mm. This method is highly reproducible and can be mass‐produced. The polarizer can cover atmospheric IR windows in both 3–5 and 7–12 μm simultaneously, which is suitable in IR imaging systems for remote sensing and astronomy observation. Abstract : Herein, a new high aspect ratio structure is designed and fabricated, which makes the polarizer have high transverse magnetic wave transmittance (TMT) and extinction ratio (ER) in 3–15 μm. This study also presents some innovations to traditional fabrication processes. These improvements make it easier to fabricate polarizers with good performance as well as large areas.